2020
DOI: 10.18502/ijph.v49i10.4681
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Household Food Basket Composition: A Systematic Review

Abstract: Background: Demographic, socioeconomic, and environmental determinants are important to population health status in all countries and diet is the main way that these factors could affect health. We aimed to conduct a systematic review of recent research evidence about these determinants of household food basket composition. Methods: The PRISMA guideline was used to the reproducibility of this systematic review. Three databases including PubMed, Scopus and Google Scholar were systematically searched from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A review of the determinants of household FB composition revealed three categories of factors affecting the contribution of different food groups in the household FB: demographic, socioeconomic, and environmental. Accordingly, we can say that these factors determine the healthiness ofahousehold diet [34].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the determinants of household FB composition revealed three categories of factors affecting the contribution of different food groups in the household FB: demographic, socioeconomic, and environmental. Accordingly, we can say that these factors determine the healthiness ofahousehold diet [34].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors are significant determinants of health in middle and low-income countries, and diet is one of the main ways that socioeconomic factors can effect on health ( 14 , 15 ). SES is represented by multiple indicators, including income, education, and occupation, all of which may operate independently or interact in leading to inequalities that influence food choices ( 16 ). Since food choice differences between socio-economic groups lead to differences in nutrient intake, better understanding socioeconomic factors that influence the household food basket is essential ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%